Spatio-Temporal Compressive Behaviors of River Pebble Concrete and Sea Pebble Concrete in Island Offshore Engineering - Yuan Yuan; Yian Zhao; Xiaotian Feng; Yanhua Lei; Wenbing Zhang (Journal of Marine Science and Engineering, 2024)
Obtaining river or sea pebbles from local resources for concrete production is considered an economical and eco-friendly alternative, particularly in marine and island-offshore engineering. However, the resulting changes in the mechanical properties of these concrete have attracted attention. This study investigates the compressive behavior of concretes where river or sea pebbles partially (i.e., 33% and 67%) or fully (i.e., 100%) replace traditional gravel as coarse aggregate, using a noncontact full-field deformation measurement system based on digital image correlation (DIC). Compared to the traditional gravel concrete (GC), compressive strengths of the river pebble concrete (RPC) at constitution rates of 33%, 67%, and 100% decreased by 6.5%, 29.8%, and 38.9% while those values of the sea pebble concrete (SPC) decreased by 13.1%, 32.7%, and 44.3%, respectively. Meanwhile, SPC exhibited slightly lower compressive strength than RPC. The peak strains of both SPC and RPC decreased at lower substitution rates, although their stress-strain curves resembled those of GC. In contrast, RPC and SPC at higher substitution rates exhibited a noticeable stage of load hardening. Full-field deformation data and interfacial characteristics indicated that the compressive failure modes of both RPC and SPC showed significant interfacial slipping between pebbles and mortar with increasing coarse aggregate substitution rates. In comparison, fractures in coarse aggregate and mortar were observed in damaged GC. The study demonstrated that the spatio-temporal compressive deformation response and failure modes of SPC and RPC were distinct due to the introduction of pebbles, providing insights for engineering applications of river/sea pebble concrete in practical offshore or island construction projects.